Perencanaan dan Analisis Keefektifan Penempatan Dinding Geser terhadap Perilaku Struktur dengan Software ETABS - Anggraini, Serina; Septiandini, Erna; Wangi, Intan Puspa (Jurnal Talenta Sipil, 2024)
The rise of high-rise building development is due to land limitations and also the soaring population. The vulnerability of high-level building structures to lateral forces, one of which is the earthquake force, requires that high-level building structures be able to withstand the lateral forces that occur. There are several structural systems in resisting lateral forces, including moment-bearing frame systems and shear wall systems. The purpose of this research is to compare the structural analysis of three alternative plans with different shear wall placements. The structural analysis uses ETABS software that refers to SNI 1726: 2019. The results of the research from three alternative models, show that the smallest deviation value towards the X-axis and Y-axis, and the average deviation value is 19.787 mm in the X-direction and 17.220 mm in the Y-direction. The requirements for a dual system with a special moment-bearing frame are also met in alternative planning 2 with a contribution of forces acting on the portal of 36.7340% in the X-direction and 31.1996% in the Y-direction. The amount of mass participation that occurs is above 90% and in accordance with the requirements specified by SNI.